Comparing individual angiotensin-converting enzyme inhibitors with losartan in the risk of hospitalization for pneumonia and related mortality: a nationwide cohort study. Issue 3 (March 2015) - Chang, Chia-Hsuin; Lin, Jou-Wei; Ruan, Sheng-Yuan; Lee, Yen-Chieh; Wu, Li-Chiu; Lin, Min-Shung; Lai, Mei-Shu
Abstract : Background: Angiotensin-converting enzyme (ACE) inhibitors might decrease the risk of pneumonia, but head-to-head comparisons with angiotensin receptor blockers (ARBs) were seldom made. The objective of this study was to evaluate incidence of pneumonia and mortality for different ACE inhibitors as compared to losartan, an ARB that has similar indications. Methods: Adult patients aged more than 20 years who initiated ACE inhibitors and losartan between 1 January 2004 and 31 December 2009 were identified from Taiwan's National Health Insurance Database. The outcomes of interest were hospitalization for pneumonia and pneumonia-related mortality. Participants were followed from treatment initiation to the earliest of outcome occurrence, death or disenrollment, treatment discontinuation, switching to other ACE inhibitors or ARBs, or study termination (31 December 31 2010). Proportional-hazards regression model was used to calculate the hazard ratios and their 95% confidence intervals (CIs), adjusted on baseline characteristics. Results: A total of 1 192 082 ACE inhibitors and 175 668 losartan initiators were included. The risk of hospitalization for pneumonia was significantly higher for captopril (hazard ratio 1.94, 95% CI 1.82–2.07), enalapril (hazard ratio 1.14, 95% CI 1.07–1.22), fosinopril (hazard ratio 1.11, 95% CI 1.02–1.21), perindopril (hazard ratio 1.14, 95% CI 1.04–1.25), and ramipril (hazard ratio 1.11, 95% CI 1.02–1.22), as compared with losartan. Captopril was associated with a significantly increased risk of pneumonia mortality (hazard ratio 2.43, 95% CI 1.79–3.31). Conclusions: Treatment with ACE inhibitors is not associated with a lower risk of pneumonia incidence and mortality as compared with losartan. Abstract : Supplemental Digital Content is available in the text